Cultural politics of Soviet government and its influence on the activities cultural institutions of Galicia in World War II (1939–1941) - Zadorozhna, Olha (Видавництво Львівської політехніки, 2013)
In this paper, it was considered the influence of the Soviet occupation regime on the activities of cultural institutions in Galicia in 1939–1941. It is important to study the prerequisites and consequences of the Soviet occupation of Western Ukraine, especially in Galicia, and to clarify the content and methods of propagation policies of the totalitarian regime and its influence on the cultural institutions, as they occupy an important role in the development of human society and national-patriotic education of the population. In recent decades, special attention is paid to the study of the cultural politics of occupation regimes in Ukraine, which allows to do a comparative analysis and to complement previously made conclusions.
Keywords: cultural policy; cultural institutions; the Second World War; the occupation regim; the Soviet government; propaganda; ideology